Pengasuhan Keluarga Terhadap Perkembangan Karakter Disiplin Anak Usia Dini pada Lingkungan Nagari Batipuh Ateh - Mawardi; Kh Jambak, Milkhatina Ummi; Suraiya; Dwidika, Naila Luthfia; Maida, Dea Rahma (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
The development of children's disciplined character is greatly influenced by the parenting patterns applied in the family, especially by parents. However, preventive efforts by parents in instilling disciplined character are still relatively minimal. This study aims to analyze and identify the relationship between family parenting patterns and the formation of children's disciplined character. Data collection was carried out through a literature review method, which includes recording research issues, aligning various findings, in-depth analysis of research results, as well as criticism and providing ideas. The results of the study revealed a relationship between parenting patterns and the development of children's disciplined character. The variety of forms of parenting contributes to differences in child development. Each parenting style, whether authoritarian, democratic, or permissive, has a different impact on children's growth in the future.